2016
DOI: 10.1097/yco.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of eating disorders in Latin America

Abstract: SPANISH ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 44 publications
9
49
0
20
Order By: Relevance
“…Austria (24) Germany (16) Switzerland (23) Norway (24) 1354 ELI countries than in Euro-American countries, whereas the pointprevalence of anorexia nervosa was lower (Kolar, Rodriguez, Chams, & Hoek, 2016). The present study appears to mirror these findings with respect to bulimia nervosa, while suggesting that anorexia nervosa might have greater salience amongst Latin American populations than epidemiological surveys have implied.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Austria (24) Germany (16) Switzerland (23) Norway (24) 1354 ELI countries than in Euro-American countries, whereas the pointprevalence of anorexia nervosa was lower (Kolar, Rodriguez, Chams, & Hoek, 2016). The present study appears to mirror these findings with respect to bulimia nervosa, while suggesting that anorexia nervosa might have greater salience amongst Latin American populations than epidemiological surveys have implied.…”
Section: Resultssupporting
confidence: 67%
“…However, the few epidemiological studies that have been conducted suggest that eating disorders in Latin America warrant further attention. A recent meta‐analysis of epidemiological research carried out in six Latin American countries found that the point‐prevalence of bulimia nervosa and binge eating disorder was higher in those countries than in Euro‐American countries, whereas the point‐prevalence of anorexia nervosa was lower (Kolar, Rodriguez, Chams, & Hoek, ). The present study appears to mirror these findings with respect to bulimia nervosa, while suggesting that anorexia nervosa might have greater salience amongst Latin American populations than epidemiological surveys have implied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nas últimas décadas, o excesso de peso e a obesidade passaram a ser um dos maiores problemas de saúde da humanidade devido ao aumento de suas prevalências em Tabela II -Prevalência do sobrepeso/obesidade, razão de prevalência e intervalo de confiança, segundo características socioeconômicas da população adulta investigada. Tefé, AM, 2015. todo o mundo (3,(5)(6)(7) . O excesso de peso tem aumentado de forma gradativa em todas as faixas etárias, desde a infância (21) até a idade adulta (14) e a sua ocorrência está associada a uma série de doenças crônico-degenerativas (14) .…”
Section: Discussionunclassified
“…Segundo os dados da Secretaria de Vigilância em Saúde do Ministério da Saúde, em 2006, o índice de indivíduos adultos com sobrepeso era de 43%, enquanto os obesos representavam 13% da população (4) . Assim como no Brasil, estudos realizados na Europa (5) , nos Estados Unidos (6) e em países emergentes da América Latina (7) também apontam para um crescimento linear e gradual no número de indivíduos com excesso de peso ou com obesidade.…”
Section: Introductionunclassified